Pengaruh Kualitas Pelayanan dan Citra Perusahaan terhadap Loyalitas Pelangan di PT Telkom - Ahyani, Ahyani; Metarini, Rr. Ayu; Budiman, Surya (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Customer loyalty is a key measure of a company's success in providing the best products and services and meeting customer needs, ensuring that customers continue to use the products sold in a sustainable manner. This poses a challenge for PT Telkom Akses as a telecommunications service provider in the midst of a highly competitive global market. This study aims to analyze the impact of service quality and company image on customer loyalty at PT Telkom Akses. The research adopts a quantitative approach with an associative design. The study involves a sample of 100 customers taken from the PT Telkom Akses database in West Jakarta. Data collection was carried out using a questionnaire developed with a Likert scale. The data analysis method employed is multiple linear regression. The findings indicate that service quality has a positive and significant effect on customer loyalty, meaning that improvements in service quality contribute to higher customer loyalty. Similarly, company image also has a positive and significant impact on customer loyalty, suggesting that a favorable image of the company enhances customer loyalty. Furthermore, both service quality and company image together influence customer loyalty, meaning that these factors combined play a significant role in fostering customer loyalty.